Tamoxifen and sodium thiosulfate reduces hepatic and renal damage induced by Xanthium strumarium L. through controlling mitochondrial permeability - Alkac, Zeliha keskin; Korkak, Fatih ahmet; Dagoglu, Gurdal; Eroksuz, Yesari; Tanyildizi, Sadettin (Polish Soc Veterinary Sciences Editorial Office, 2025)
Xanthium strumarium is toxic and causes cell death as a result of oxidative stress and mitochondrial dysfunction. Tamoxifen (TAM) is an anticancer agent that prevents the opening of mitochondrial permeability transition pores (mPTP) and the formation of reactive oxygen species (ROS). Sodium thiosulfate (STS) is a hepatoprotective agent with antioxidant effect. In this study, the therapeutic effects of TAM and STS on liver and kidney toxicity caused by X. strumarium were investigated. For this purpose, 35 female SpragueDawley rats were used. Rats were administered TAM and STS 6 and 24 hours after X. strumarium seeds extract administration. The rats were sacrificed 2 hours after the last administration. Increased serum biochemistry parameters and decreased glucose levels following X. strumarium toxicity approached the control group with TAM and STS treatment. Oxidative stress, which was more pronounced in liver tissue, decreased with TAM and STS treatment. mPTP opening was blocked by TAM-containing groups, whereas the increased ATP-synthase activity was decreased by TAM and STS alone and in combination. However, both compounds were effective in reducing histopathologic damage limited to liver tissue. The reduction of liver and kidney damage by TAM and STS in X. strumarium toxicity suggests the potential use of these compounds for treatment in case of poisoning.
Keywords: Xanthium strumarium; tamoxifen; sodium thiosulphate; histopathology; immunohistochemistry